Respuesta :

A positive + A positive = A positive (1+2=3)

A negative + A negative = A negative (-1+(-2)=-3)

Adding a negative is like subtracting a positive (1 + (-2) = -1) this is equal to (1 - 2 = -1)

Adding a positive is like subtracting a negative (-1 + 2 = 1)

Answer:

A positive + A positive = A positive (1+2=3)

A negative + A negative = A negative (-1+(-2)=-3)

Adding a negative is like subtracting a positive (1 + (-2) = -1) this is equal to (1 - 2 = -1)

Adding a positive is like subtracting a negative (-1 + 2 = 1)

ACCESS MORE
EDU ACCESS
Universidad de Mexico